Pengaruh Harga dan Cita Rasa Terhadap Kepuasan Konsumen pada Kebuli Curry House Karawang - Eka Ashri Nurhamidah; Netti Nurlenawati; Dexi Triadinda (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
“Kebuli Curry House is one of the restaurants that sells Middle Eastern specialties, namely Kebuli rice in Karawang. The purpose of this study is to understand the effect of price and taste on customer satisfaction. This research is categorized as quantitative research based on its objectives. Data was collected by distributing questionnaires to 96 respondents online and offline. The purposive sampling method was used for the sampling technique using purposive sampling conditional on the respondent having made a purchase either directly or online as well as eating food from Kebuli Curry House Karawang at least once. Furthermore, multiple linear regression analysis was performed on this data. The results show that price has an insignificant effect on customer satisfaction, while taste has a significant effect on customer satisfaction.”